Evaluation of the female reproductive toxicity of aqueous extract of Labisia pumila var. alata in rats - M.F., Wan Ezumi (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2009)
Objective: To detect potenti~I acfverse effects of aqueous xtract of Labisia pumila var. alata (LPE) or 'Kacip Fatimah''on the estrous cycle, rzpro ctive performance, post-natal growth and offspring survival of rats. Materials and Methods: Forty eight (48) female Sp gue Dawley rats with consecutive 4 to 6 days estrous cycle were given distilled water (as control) or LPE at 2, 20, 200, 400 or 800 mg/kg daily by gavaging ten days prior to mating, mating (a maximum period of ten days), gestation and lactation periods of seven days. Dams and fetuses were sacrificed on day seven postnatal. Results: Labisia pumila extracts did not alter the estrous cycle and general health of all rats. All the animals proceed towards successful mating and pregnancies. There was no significant difference in the duration of pregnancy and all pregnant rats delivered normally. Statistically no test agent-related changes in the maternal body weight, number of implantations, litter size and pup body weights were observed. Other parameters measured include pup sex ratio, live birth index, pup viability index and percentage of implantation death which also showed no significant difference. <:;onclusion: The present findings indicate that water based extracts of Labisia pumi/a var. a/ala do not pose any significant reproductive toxicity or complication in pregnancy and delivery in rats. The extract did not significantly a lter the duration of pregnancy in rats, however the duration of delivery was not evaluated in this study .